Regulation of sugar transport via the multiple sugar metabolism operon of Streptococcus mutans by the phosphoenolpyruvate phosphotransferase system. - Cvitkovitch, D G (1995)
In this report, we provide evidence that the transport of sugars in Streptococcus mutans via the multiple sugar metabolism system is regulated by the phosphoenolpyruvate phosphotransferase system. A ptsI-defective mutant (DC10), when grown on the multiple sugar metabolism system substrate raffinose, exhibited reduced growth, transport, and glycolytic activity with raffinose relative to the parent strain BM71. Inhibition of [3H]raffinose uptake was also observed in both BM71 and DC10 with increasing concentrations of glucose and the glucose analogs alpha-methyl glucoside and 2-deoxyglucose.